IScale: Studying long-term experiences through memory - Karapanos, Evangelos (My University, 2013)
This chapter presents iScale, a survey tool for the retrospective elicitation of longitudinal user experience data. iScale aims to minimize retrospection bias and employs graphing to impose a process during the reconstruction of one's experiences. Two versions, the constructive and the value-account iScale, were motivated by two distinct theories on howpeople reconstruct emotional experiences from memory. These two versions were tested in two separate studies. Study 1 aimed at providing qualitative insight into the use of iScale and compared its performance to that of free-hand graphing. Study 2 compared the two versions of iScale to free recall, a control condition that does not impose structure on the reconstruction process. Overall, iScale resulted in an increase in the amount, the richness, and the test-retest consistency of recalled information as compared to free recall. These results provide support for the viability of retrospective techniques as a cost-effective alternative to longitudinal studies.
Keywords: Free Recall; Episodic Memory; Temporal Information; Semantic Memory; Experience Report